The Influence of The Discovery Learning Learning Model Using Canva Media On Students Critical Thinking Abilities In Class XI History Learning At MAN - Suci, Sekar Wulan; Syarif Hadi Wibowo, Tubagus Umar; Maryuni, Yuni (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This research was conducted with the aim of finding out the effect of the discovery learning model using Canva media on students' critical thinking abilities in class XI history learning at MAN 1 Lebak. The research method used was a quasi experiment with a "pretest posttest control group design" using two groups, namely the experimental class and the control class. The research results obtained using the T-test obtained sig. (2-tailed) = 0.01 < 0.05, so H1 is accepted and H0 is rejected. These results state that there is an influence of using the discovery learning model with Canva media on the critical thinking abilities of class XI students at MAN 1 Lebak.